Bureaucracy and democracy : accountability and performance - Gormley, William T., Jr., 1950-; Balla, Steven J. (Washington, D.C. : CQ Press, 2013)
Given the influence of public bureaucracies in policy implementation, Gormley and Balla assess their performance using four key perspectives--bounded rationality, principal-agent theory, interest group mobilization, and network theory--to help students develop an analytic framework for evaluating bureaucratic accountability.
Bureaucracies as policymaking organizations -- Bureaucratic reasoning -- The bureaucracy's bosses -- The bureaucracy's clients -- Bureaucratic networks -- The politics of disaster management -- Why are some bureaucracies better than others?
Includes bibliographical references and index.
Keywords: Bureaucracy -- United States